PENGARUH PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PERUBAHAN LINGKUNGAN DI SMAS PANCA BUDI MEDAN - Afifah Siregar, Rara; Ashar Hasairin; Rosliana Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of implementing the Problem-Based Learning (PBL) model with the aid of Wordwall media on students' critical thinking skills in the topic of environmental change. The method used was a quasi-experimental design with a Pretest–Posttest Control Group Design at Panca Budi Private High School, Medan. The study population included all 10th-grade students, with the sample selected using cluster random sampling. The research instrument was a critical thinking essay test referring to the six Facione indicators: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using an Independent Sample t-test after undergoing prerequisite tests for normality and homogeneity. The results showed that the average posttest score of the experimental class (79.62) was higher than that of the control class (73.95). The hypothesis test yielded a significance value of 0.002 (p < 0.05), indicating that the integration of the PBL model with Wordwall media significantly improved students' critical thinking skills. The integration of interactive media in problem-based learning has been shown to create a more active, contextual, and effective learning experience in supporting the development of students' higher-order thinking skills in Biology.